2022
DOI: 10.1093/gbe/evac112
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogenetic Position of the Enigmatic, Polypodium hydriforme (Cnidaria, Polypodiozoa): Insights from Mitochondrial Genomes

Abstract: Polypodium hydriforme is an enigmatic parasite that belongs to the phylum Cnidaria. Its taxonomic position has been debated: while it was previously suggested to be part of Medusozoa, recent phylogenomic analyses based on nuclear genes support the view that P. hydriforme and Myxozoa form a clade called Endocnidozoa. Medusozoans have linear mitochondrial (mt) chromosomes while myxozoans, as most metazoan species, have circular chromosomes. In this work, we determined the structure of the mt genome of P. hydrifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Specifically, while the size of a circular animal mitogenome can be >40 kb, the size of most circular animal mitogenomes are <20 kb ( Desalles et al 2017 ). While a tube worm has the largest linear mitogenome reported to date (>80 kb; Stampar et al 2019 ), a recent study has reported a >90 kb circular mitogenome in a cnidarian species ( Novosolov et al 2022 ). In insects, the mitogenome size has often been reported to be around 15–16 kb ( Cameron 2014 ; Desalle et al 2017 ; but exceptionally large mitogenomes have been found in bark weevils; Boyce et al 1989 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, while the size of a circular animal mitogenome can be >40 kb, the size of most circular animal mitogenomes are <20 kb ( Desalles et al 2017 ). While a tube worm has the largest linear mitogenome reported to date (>80 kb; Stampar et al 2019 ), a recent study has reported a >90 kb circular mitogenome in a cnidarian species ( Novosolov et al 2022 ). In insects, the mitogenome size has often been reported to be around 15–16 kb ( Cameron 2014 ; Desalle et al 2017 ; but exceptionally large mitogenomes have been found in bark weevils; Boyce et al 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tandem repeats have been an interesting evolutionary phenomenon in the control region of animal mitochondria not only because of their phylogenetic and systematic utilities ( Faber and Stepien 1997 ; Mundy and Helbig 2004 ; Wan et al 2012 ; Wang et al 2015 ; Novosolov et al 2022 ), but also because of their evolutionary dynamics and the implication on mitochondrial function ( Mundy and Helbig 2004 ; Saito et al 2005 ; Yuan et al 2015 ; Chen et al 2020 ; Kinkar et al 2021 ; Novosolov et al 2022 ). For example, we found that in Dynastes mitogenomes, the 206 bp tandem repeats were closely located both prior to and after the conserved sequence blocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cnidarians have been shown to harbor a wide-range of mt-genome phenotypes, including the “traditional” single circular chromosome, multiple circular chromosomes, a single linear chromosome, or a highly fragmented genome ( fig. 2 ) ( Bridge, et al 1992 ; Kayal, et al 2012 ; Novosolov, et al 2022 ; Osigus, et al 2013 ; Smith, et al 2012 ; Yahalomi, et al 2017 ). The mitochondrion is also typically described as being essential and omnipresent in contemporary eukaryotes, but mitochondrial genomes in “early-branching” eukaryotes are frequently reduced ( Santos, et al 2018 ), or lost altogether ( John, et al 2019 ; Karnkowska, et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%